2017
DOI: 10.1007/s00787-017-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory control of carbon dioxide in children and adolescents referred for treatment of psychogenic non-epileptic seizures

Abstract: Psychogenic non-epileptic seizures (PNES) are a common problem in paediatric neurology and psychiatry that can best be understood as atypical responses to threat. Threats activate the body for action by mediating increases in arousal, respiration, and motor readiness. In previous studies, a range of cardiac, endocrine, brain-based, attention-bias, and behavioral measures have been used to demonstrate increases in arousal, vigilance, and motor readiness in patients with PNES. The current study uses respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 60 publications
(59 reference statements)
4
39
1
Order By: Relevance
“…Under task conditions, they showed an increased cortical response to an auditory stimulus (suggesting activation of brain arousal systems) ( Kozlowska, Melkonian, Spooner, Scher, & Meares, 2017 ) and increased motor readiness to emotion faces (suggesting activation of the motor system) ( Kozlowska, Brown, Palmer, & Williams, 2013 ). In the current cohort of 60 children/adolescents with PNES, in the baseline eyes-open, resting state-condition, we also found that our patients (vs controls) showed increased heart rates and increased respiratory rates ( Kozlowska, Rampersad, et al, 2017 ), consistent with the coupling between sympathetic arousal (which innervates the cardiac motor system) and the respiratory motor system. In one child in the sample, we also documented (via laryngoscopy) that the child activated an abnormally robust motor response in her larynx – adduction of the vocal chords – when she became frightened, distressed and highly aroused, resulting in cerebral hypoxia and a hypoxia-related non-epileptic seizure.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Under task conditions, they showed an increased cortical response to an auditory stimulus (suggesting activation of brain arousal systems) ( Kozlowska, Melkonian, Spooner, Scher, & Meares, 2017 ) and increased motor readiness to emotion faces (suggesting activation of the motor system) ( Kozlowska, Brown, Palmer, & Williams, 2013 ). In the current cohort of 60 children/adolescents with PNES, in the baseline eyes-open, resting state-condition, we also found that our patients (vs controls) showed increased heart rates and increased respiratory rates ( Kozlowska, Rampersad, et al, 2017 ), consistent with the coupling between sympathetic arousal (which innervates the cardiac motor system) and the respiratory motor system. In one child in the sample, we also documented (via laryngoscopy) that the child activated an abnormally robust motor response in her larynx – adduction of the vocal chords – when she became frightened, distressed and highly aroused, resulting in cerebral hypoxia and a hypoxia-related non-epileptic seizure.…”
Section: Introductionsupporting
confidence: 76%
“…Limitations have been discussed in previous publications ( Kozlowska, Rampersad, et al, 2017 ) ( Kozlowska, Catherine, et al, 2017 ). An additional limitation in this study was the small number of patients ( n = 2) with intellectual disability.…”
Section: Discussionmentioning
confidence: 96%
“…Other clinical characteristics, intelligence quotient, comorbid neurological conditions and the semiology of PNES are documented in Tables 2 and 3 . All children in the study participated in the PNES Hyperventilation Study, which provided neurophysiological data and HV-challenge profiles ( Kozlowska, Rampersad, et al, 2017 ). Eight children/adolescents were excluded from the previous study because of partial pressure of carbon dioxide (PCO 2 ) data were not collected, and four because PCO2 data were inadequate (technical difficulties or child’s lack of cooperation during the HV challenge).…”
Section: Methodsmentioning
confidence: 99%
“…We had also observed that many of our patients with PNES hyperventilated in and around the time of their PNES, and that HV appeared to trigger their PNES. We formally tested this hypothesis in the scientific arm of this study – the PNES Hyperventilation Study ( Kozlowska, Rampersad, et al, 2017 ). We found that nearly half of the children/adolescents with PNES (26 of 60) had difficulty in regulating CO 2 during a HV-challenge, and that over half those with PNES (32 out of 60) appeared to trigger their events with HV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation